Streaming Channel Brand’s Rhetoric through @NetflixID Twitter Account - Hamdiki Ainur Roziqi; Nia Ashton Destrity (CHANNEL: Jurnal Komunikasi, 2022)
This research aims to analyze the rhetoric of @NetflixID, well-known as a brand's Twitter account using Selzer's rhetorical analysis approach. Data was collected in January 2020 through documentation using the text analysis technique. The objective of this research is to analyze @NetflixID's rhetoric and show that @NetflixID was found to be embodied the human character by using humor, emojis and emoticons, authorship and personal pronouns, non-formal language style, choice of words, anecdote, and non-standard vocabularies in giving information and showing emotions. Canon style and canon memory help find the pathos and logos of @NetflixID. Furthermore, this research found the potential uses of conversational tone, authorship, and personal pronouns as a marketing communication tool in initiating social interactions, generating affective responses from the audience, creating emotional bonds with the consumer, and attracting the consumers' attention similarly to humor. After all, this research discovers @NetflixID's rhetoric in promoting the products and engaging with audiences.